HUBUNGAN PENGETAHUAN, SIKAP BENCANA DAN KETERAMPILAN BASIC LIFE SUPPORT DENGAN KESIAPSIAGAAN BENCANA GEMPA BUMI PADA MAHASISWA KEPERAWATAN POLTEKKES BANDA ACEH - Budimanto .; Mudatsir .; Teuku Tahlil (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Aceh is a region that is highly prone to natural disasters, such as earthquakes. One of them was the 6.2 magnitude earthquake that struck Aceh Tengah and Bener Meriah Regencies and killed 42 people in 2013. Basic Life Support is a level of medical care which is used for victims of natural disasters with or without trauma. The objective of this research was to correlate knowledge, attitude, and Basic Life Support skill of nursing students in Aceh Health Polytechnic to their earthquake preparedness. The research was conducted by employing quantitative method with cross-sectional study approach. The data were collected by using questionnaires and observation sheets and were then analyzed by using Chi-square test. There were eighty seven samples chosen. Sixty one samples were female while the others were male aged 19-21. It was found that the knowledge of most of the samples was in good category (51,7%), their attitude was mostly in poor category (75,9%), and their Basic Life Support skill was in fair category (60%). Moreover, the bivariate analysis indicated that the knowledge of most of the samples was in good category (63,9%), their attitude was also in good category (71,4%), and their skill was in fair category (61,1%). Hence, it can be concluded that the knowledge and attitude of the nursing students in Aceh Health Polytechnic were significantly correlated to the students’ preparedness (p=0,005) while their Basic Life Support skill was not (p=0,594).